PELATIHAN PENYUSUNAN USULAN PENELITIAN BAGI GURU BIMBINGAN DAN KONSELING SMP DI KABUPATEN PESAWARAN - Syarifuddin Dahlan; Mujiyati Mujiyati; Ranni Rahmayanthi; Saikhoni Saikhoni (Bagimu Negeri, 2022)
Abstract: Teachers in secondary schools, including Guidance and Counseling Teachers (BK teachers) in junior high schools, should be accustomed to conducting research, especially action research. In fact, it is still often found that BK teachers have not been able to conduct research in accordance with the demands and conditions of scientific research. This activity aims to help BK teachers design a guidance and counseling research. The training was carried out in Pesawaran District which was attended by 38 participants using the work-task learning method in the form of a workshop. The activity begins with briefing and continues with the practice of preparing research proposals in a guided manner. Evaluation of the achievement of activities is carried out to check the level of teacher skills in preparing action research designs correctly using the Action Research Design Quality Assessment Form. The results of the activity showed that in general the skills of the participants had improved. They have been able to formulate the title, problem, objective, and research methodology correctly. Participants categorized as "Highly Skilled" = 13,15%, "Skilled" = 34,20%, and "Sufficiently Skilled" = 26.30%, "Less Skilled" = 21,10.50%, the rest, around 5,25% are still in the category " Very Unskilled.” Based on the results of the evaluation of activities, it is recommended that this kind of training be followed up by increasing the intensity of the debriefing and expanding the target audience.